In-column ATR-FTIR spectroscopy to monitor affinity chromatography purification of monoclonal antibodies - Boulet-Audet,M; Kazarian,SG; Byrne,B (Scientific Reports, 2016)
In recent years many monoclonal antibodies (mAb) have entered the biotherapeutics market, offering new treatments for chronic and life-threatening diseases. Protein A resin captures monoclonal antibody (mAb) effectively, but the binding capacity decays over repeated purification cycles. On an industrial scale, replacing fouled Protein A affinity chromatography resin accounts for a large proportion of the raw material cost. Cleaning-in-place (CIP) procedures were developed to extend Protein A resin lifespan, but chromatograms cannot reliably quantify any remaining contaminants over repeated cycles. To study resin fouling in situ, we coupled affinity chromatography and Fourier transform infrared (FTIR) spectroscopy for the first time by embedding an attenuated total reflection (ATR) sensor inside a micro-scale column while measuring the UV 280 nm and conductivity. Our approach quantified the in-column protein concentration in the resin bed and determined protein conformation. Our results showed that Protein A ligand leached during CIP. We also found that host cell proteins bound to the Protein A resin even more strongly than mAbs and that typical CIP conditions do not remove all fouling contaminants. The insights derived from in-column ATR-FTIR spectroscopy monitoring could contribute to mAb purification quality assurance as well as guide the development of more effective CIP conditions to optimise resin lifespan.